Theory-based self-management intervention to improve adolescents’ asthma control: a cluster randomised controlled trial protocol - Harris, Katherine (BMJ Open, 2019)
INTRODUCTION: Asthma-related morbidity and mortality in the UK is higher than elsewhere in Europe. Although the reasons for this are largely unclear, one explanation could be a higher prevalence of poorly controlled asthma in the UK. Findings from our earlier study found that, in a sample of 766 children with asthma, 45.7% had poorly controlled asthma. Our earlier study also showed that adherence to inhaled corticosteroids was low. Subsequent focus groups identified concerns regarding embarrassment and bullying as barriers to adherence, as well as forgetfulness and incorrect medication beliefs. Following this, a school-based self-management intervention has been developed, aimed to improve asthma control and self-management behaviours. METHODS AND ANALYSIS: The theory-based cluster randomised controlled trial tests an intervention comprising two components: (1) a theatre workshop for all children in years 7 and 8, and (2) self-management workshops for children with asthma. The COM-B model was used to guide the development of the intervention. Questionnaire data will be collected in schools at baseline, immediately post intervention, and 3, 6 and 12 months post intervention. The data collected at 6 months will measure the effect of the intervention against the baseline data. The primary outcome will be asthma control, measured using the Asthma Control Test. All the data will be analysed quantitatively using generalised linear and non-linear mixed effects models. ETHICS AND DISSEMINATION: Ethical approval was obtained by the Queen Mary University of London Ethics Committee on 12 April 2018. Regular meetings will be held with key patient and public stakeholders to plan the key messages from this research. Key messages from the study will also be tweeted via the project twitter account (@SchoolsAsthma). The findings of the study will be submitted for presentation at conferences, as well as written into a manuscript. TRIAL REGISTRATION NUMBER: MGU0400